Studi Literatur: Penetapan Kadar Bahan Kimia Obat Natrium Diklofenak Pada Sediaan Jamu Menggunakan Metode Kromatografi Lapis Tipis Dan Spektrofotometri UV-Vis - Jacinda Caroline Nathania; Siska Rusmalina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Herbal medicine is a traditional medicine that is in great demand because it is made from natural ingredients with minimal side effects. This creates irresponsible producers who add BKO to increase sales. One of the medicinal chemicals that is often added is diclofenac sodium. The aim of this research is to review the journal of medicinal chemical analysis (BKO) of sodium diclofenac in herbal medicine in order to determine the effectiveness of the stationary phase and mobile phase in the thin layer chromatography method and the effectiveness of the solvent in UV-Vis spectrophotometry in the analysis of the medicinal chemical of sodium diclofenac in preparations herbal medicine. This research method is a literature study, by searching for articles on the Google Scholar database. Some of the keywords used include solvent optimization in the analysis of diclofenac sodium in herbal medicine preparations using the TLC method and UV-Vis spectrophotometry, optimization and validation of determining the levels of diclofenac sodium in herbal medicine preparations using the TLC method and UV-Vis spectrophotometry, analysis of diclofenac sodium in herbal medicine preparations. using the TLC method and UV-Vis spectrophotometry, and validation of determining the levels of diclofenac sodium in herbal preparations using the TLC method and UV-Vis spectrophotometry. The search strategy is limited by using several filters, including publication year between 2018 – 2023, selection of full text type and English and Indonesian. This research method is a literature study, by searching for articles on the Google Scholar database. Some of the keywords used include solvent optimization in the analysis of diclofenac sodium in herbal medicine preparations using the TLC method and UV-Vis spectrophotometry, optimization and validation of determining the levels of diclofenac sodium in herbal medicine preparations using the TLC method and UV-Vis spectrophotometry, analysis of diclofenac sodium in herbal medicine preparations. using the TLC method and UV-Vis spectrophotometry, and validation of determining the levels of diclofenac sodium in herbal preparations using the TLC method and UV-Vis spectrophotometry. The search strategy is limited by using several filters, including publication year between 2018 – 2023, selection of full text type and English and Indonesian.